2021
DOI: 10.1515/znc-2021-0142
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofOriganum dubium, Origanum vulgaresubsp.hirtum, and Lavandula angustifoliaessential oils on lipid profiles and liver biomarkers in athletes

Abstract: This study aims to determine the effects of essential oils of Origanum dubium (DUB), Origanum vulgare subsp. hirtum (HIR), and Lavandula angustifolia (LAV) on lipid profiles and liver biomarkers in athletes. Thirty-four trained athletes were randomly assigned to one of three experimental groups or the control group (CON). The concentrations of serum lipids and liver biomarkers were assessed before and after the 14-day essential oil intervention. Gas chromatography-mass spectrometry analysis showed 68.0 and 82.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The subjects were divided into four groups (control, DUB, HIR and LAV) and received 2 mL EO three times a day (diluted in 150 mL of warm water after each meal) for two weeks. HDL-C significantly increased in DUB and HIR groups and LDL-C significantly decreased in the DUB group only [ 36 ]. Another study reported that treatment of patients with mild hyperlipidaemia by Origanum onites supplement (25 mL of the aqueous distillate of Origanum onites for three months) elicited a significant increase in HDL-C and a significant decrease in LDL-C compared to the controlled group [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were divided into four groups (control, DUB, HIR and LAV) and received 2 mL EO three times a day (diluted in 150 mL of warm water after each meal) for two weeks. HDL-C significantly increased in DUB and HIR groups and LDL-C significantly decreased in the DUB group only [ 36 ]. Another study reported that treatment of patients with mild hyperlipidaemia by Origanum onites supplement (25 mL of the aqueous distillate of Origanum onites for three months) elicited a significant increase in HDL-C and a significant decrease in LDL-C compared to the controlled group [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methyl alcohol solution was evaluated as a blank sample. Radical scavenging activity (%) was calculated from the equation = [(A Control -A Sample ) / A Control ] ×100 (Maral et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Detector, injector, and ion source temperatures were 270°C, 250°C, and 230°C, respectively. MS scan range was (mz-1): 50-550 atomic mass units (AMU) under electron impact (EI) ionization of 70 eV (Maral et al, 2022).…”
Section: Methodsmentioning
confidence: 99%